Employment and Welfare Effects of a Two-Tier Unemployment Compensation System - Burkhard Heer (Center for Economic Studies and ifo Institute (CESifo), 2000)
In many OECD countries, e.g. in Germany, France, or the UK, unemploy-ment compensation consists of unemployment insurance and unemployment assistance. Unemployment assistance is provided subsequent to the expiration of entitlement to unemployment insurance and is lower. The effects of this two-tier unemployment compensation system are studied in a general equilibrium job search model with endogenous distributions of in-come, wealth, and employment which is calibrated with regard to the charac-teristics of the German economy. Our results are as follows: i) employment is a decreasing function of both unemployment insurance and unemployment assistance. ii) Savings are (not) a monotone increasing function of unemployment insurance (unemployment assistance payments). iii) Optimal unemployment compensation payments are found to be a decreasing function over time.
Keywords: 330; Unemployment compensation; search unemployment; general equilibrium; overlapping generations